Suppression of angiogenesis and tumor growth by the inhibitor K1–5 generated by plasmin-mediated proteolysis - Cao, Renhai (The National Academy of Sciences, 1999)
Proteolytic enzymes are involved in generation of a number of endogenous angiogenesis inhibitors. Previously, we reported that angiostatin, a potent angiogenesis inhibitor, is a proteolytic fragment containing the first four kringle modules of plasminogen. In this report, we demonstrate that urokinase-activated plasmin can process plasminogen to release an angiogenesis inhibitor, K1–5 (protease-activated kringles 1–5). K1–5 inhibits endothelial-cell proliferation with a half-maximal concentration of approximately 50 pM. This inhibitory effect is endothelial-cell-specific and appears to be at least approximately 50-fold greater than that of angiostatin. A synergistic efficacy of endothelial inhibition was observed when angiostatin and kringle 5 (K5) were coincubated with capillary endothelial cells. The synergistic effect is comparable to that produced by K1–5 alone. Systemic treatment of mice with K1–5 at a low dose significantly blocked the fibroblast growth factor-induced corneal neovascularization, whereas angiostatin had no effect at the same dose. K1–5 also suppressed angiogenesis in chicken embryos. Systemic administration of K1–5 at a low dose at which angiostatin was ineffective significantly suppressed the growth of a murine T241 fibrosarcoma in mice. The antitumor effect correlates with the reduced neovascularization. These findings suggest that the plasmin-mediated proteolysis may be involved in the negative switch of angiogenesis.